2017
DOI: 10.2147/ndt.s132516
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment for psychomotor agitation in neuromyelitis optica spectrum disorder with trazodone–risperidone combination: a case report

Abstract: Neuromyelitis optica (NMO) is a relapsing disease that typically affects the spinal cord and optic nerves. So far, a few studies have reported pharmacologic treatment for psychiatric symptoms in patients with NMO spectrum disorder (NMOSD). However, no literature has described psychomotor agitation associated with the disease and its treatment. We report an 84-year-old woman with NMOSD whose psychomotor agitation was effectively treated with a combination of trazodone and risperidone. Our observation suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Her catatonia was treated with lorazepam (1.5 mg/day). Finally, an 84-year-old Japanese woman suddenly began to cry loudly and became aggressive toward her husband [10]. She became violent and occasionally slapped him.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her catatonia was treated with lorazepam (1.5 mg/day). Finally, an 84-year-old Japanese woman suddenly began to cry loudly and became aggressive toward her husband [10]. She became violent and occasionally slapped him.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based survey indicated that the prevalence of psychotic disorders in MS patients is approximately 1.5% [7]. In addition, little information Corresponding Author: Norio Yasui-Furukori, MD, PhD, Department of Neuropsychiatry, Hirosaki University, School of Medicine, Hirosaki 036-8562, Japan; Tel: +81-172-39-5066, Fax: +81-172-39-5067, E-mail: yasufuru@hirosaki-u.ac.jp exists regarding neuropsychiatric symptoms in NMOSD patients, although several reports have suggested that neuropsychiatric symptoms, such as paranoia [8], catatonia [9] and psychomotor agitation [10], occur in these patients. In particular, few reports on NMOSD have described a severe hallucinatory-paranoid state similar to that of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%